(untitled) (Research, Society and Development, 2022)
Objective: to describe the process of developing and validating an educational infographic on safety in medication administration for patients and their families. Methodology: methodological study developed according to the instructional design steps and carried out in an adult surgical inpatient unit. Its validation was performed by 12 specialists, 16 patients and 14 family members using the Content Validation Index (CVI) with a rate of 0.9. Results: In the validation by experts, the total CVI was 0.94 and the material’s ability to visually help remember safety barriers was observed. In the validation by patients and family members, the total CVI was 0.97, evidencing the need for language improvements. Conclusion: The infographic as an educational strategy, demonstrated the potential of this resource to equip patients and families, making information about safety aspects in medication administration accessible and acting as a support tool in health education.